The Theoretical and Practical Rationale for the Role of Regional Development Funds in the Economy - Korenik, Dorota (Teoretyczne i praktyczne uzasadnienie roli regionalnych funduszy rozwoju w gospodarce, 2023)
The aim of the paper was to formulate a theoretical basis to justify the role of a specific financial institution, i.e. the Regional Development Fund (RDF), in the regional economy, and to establish the actual role of Regional Development Funds (RDFs) in Poland. The concept of comparative finance was used. Based on the principle of inference per analogiam in terms of the RDFs’ belonging to the market financial sector, the classical paradigm of financial intermediation and the paradigm transpositions of the bank’s role in the economy were used, and, complementarily, paradigms specific to public finance. In terms of establishing the actual role in the Polish reality, a descriptive method was used, after desk research analysis of RDFs financial reports, Investment Strategy documents, reports of the Association of Regional Development Funds. Theoretical paradigms appropriate to the specifics of the Regional Development Fund were obtained to explain its position in the region’s economy, moreover, the true role of such institutions in the Polish economy was established. The multidimensionality of the RDF’s role in the economy and its dual nature should be explained on the basis of paradigms of financial intermediation in their fusion with paradigms of the role of public finance. There are no arguments strong enough to undermine the legitimacy of the existence of current RDFs in Poland, yet it cannot be stated unequivocally that Polish RDFs perform sufficiently well in the assigned dual role. There are areas for improvement (the incentive system and the operational criteria in the Investment Strategies), which could significantly improve the usefulness of RDFs in the economy of the regions.
Financial Sciences. Nauki o Finansach, 2023, vol. 28, no. 2, s. 11-20
Keywords: financial institutions; financial intermediation; financial system; regional development funds; instytucja finansowa; pośrednictwo finansowe; system finansowy